Reduced Baseline Sensitivity to Maraviroc Inhibition Among R5 HIV-1 Isolates From Individuals With Severe Immunodeficiency. (1st March 2016) - Karlsson, Ulf; Repits, Johanna; Antonsson, Liselotte; Cederfjäll, Erik; Ljungberg, Bengt; Ålenius, Martin; Sabirsh, Alan; Gisslen, Magnus; Esbjörnsson, Joakim; Jansson, Marianne
Abstract : Supplemental Digital Content is Available in the Text.